AUDIT OF THE AUDITS - Alam, Malik Mahmood (Journal of Ayub Medical College Abbottabad, 2015)
Audits play an important role in improving the services to patient care. Our department was involved in carrying out Audits by the trainees on regular basis as suggested by the Royal college and each House officer or the Registrar rotating through was doing an Audit in his/her tenure. Ninteen Audits were done in 3 years in the Pediatric department. We used the criteria suggested for evaluating the quality of Audits and put into the category of full Audits, Partial Audits, Potential Audits and planning Audits. Six of our Audits were full Audits, eleven were partial Audits, two were Potential Audits and none were Planning Audits. We think that as a general trend we had similar shortcomings in quality of our Audits which need to be improved by involving seniors specially in implementing the changes suggested in the Audits otherwise it will not fulfill the Aims and objectives. Keywords: Audit of the Audits, Audit quality ,Audit cycle